RANCANG BANGUN APLIKASI MONITORING ALAT PEMBERI PAKAN IKAN OTOMATIS BERBASIS WEB MENGGUNAKAN PROTOKOL HYBRID WEBSOCKET DAN MQTT DENGAN METODE MODEL V - Muhammad Al Fatih; Sartika Lina Mulani Sitio (Journal of Research and Publication Innovation, 2025)
Freshwater fish farm is one of the most profitable industrial sectors in Indonesia. With a tropical climate and high market demand, freshwater fish farm widely practiced by our community. However, technological advancements are still minimally applied in this sector. The development of a special device that can provide scheduled fish feeding and can be configured via a mobile application would greatly assist the operations of freshwater fish farmers in our country. This device can solve several problems in this sector including the number of human resources, negligence in feeding schedules, and errors in feed quantity. This research was conducted using methods of observation, literature study, and system design with the aim to designing and building an IoT-based (Internet of Things) feeder device. The system is integrated with the Arduino IoT Cloud service as a server for the application and device, allowing users to control the feeder device using the Arduino IoT Remote application available on smartphones. The feeder device is designed using Wemos D1 Mini ESP8288 as the microcontroller, HC-SR04 ultrasonic sensor to detect remaining feed in the feeder tube, relay module to control the motor, and synchronous motor to dispense the feed. The development of this tool is expected to contribute to the implementation of technological advancements in all industrial sectors in our country.